Biological adhesion in seagrasses: The role of substrate roughness in Posidonia oceanica (L.) Delile seedling anchorage via adhesive root hairs. (September 2020) - Zenone, A.; Alagna, A.; D'Anna, G.; Kovalev, A.; Kreitschitz, A.; Badalamenti, F.; Gorb, S.N.
Abstract: Seagrasses are marine flowering plants that developed several adaptive traits for living in submerged waters. Among this group, Posidonia oceanica (L.) Delile is the dominant species of the Mediterranean Sea, forming persistent meadows that provide valuable ecosystem services to human communities . P. oceanica seedlings can anchor to rocky substrates through adhesive root hairs. Here we investigate, for the first time, the bioadhesion process in seagrasses. Seedlings were grown on substrates provided with different roughness in order to identify mechanisms involved in the adhesion process. Root anchorage strength was measured through a peel test and hair morphology at different micro-roughness was analysed by electron and fluorescence microscopy. Maximum anchorage strength was recorded at roughness levels between 3 and 26 μm, while on finer (0.3) and coarser (52, 162 μm) roughness attachment was weaker. No attachment was obtained on smooth surfaces. Accordingly, root hair tip morphology strongly responded to the substrate. Morphological adaptation of the root hairs to surface topography and mechanical interlocking into the micro-roughness of the substrate appear the main mechanisms responsible for bioadhesion in the system under study. Substrate roughness at the scale of microns and tens of microns is pivotal for P. oceanica seedling attachment to take place. These findings contribute to identification of features of optimal microsite for P. oceanica seedling settlement and to the development of novel approaches to seagrass restoration that take advantage of species' key life history traits. Highlights: P. oceanica seedlings are able to attach to rocky substrates via adhesive root hairs. Here the bioadhesion process, observed also in other seagrasses, is investigated. Adhesion strength and hair morphology at different micro-roughness were analysed. Maximum adhesion strength was recorded at roughness between 3 and 26 μm. Mechanical interlocking of root hair tips resulted the main bioadhesion mechanism.